2021
DOI: 10.1186/s12935-021-02404-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HCP5 as a potential therapeutic target and prognostic biomarker for various cancers: a meta‑analysis and bioinformatics analysis

Abstract: Background Accumulating studies indicated that dysregulated long non-coding RNA human histocompatibility leukocyte antigen (HLA) Complex P5 (HCP5) may functions as an potential prognostic predictor in multiple cancers. This meta-analysis was performed to systematically collect studies and conduct an evidence-based evaluation of the prognostic role of HCP5 in malignancies. Methods Four databases (PubMed, Web of Science, Embase and Cochrane library) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…HCP5 affects tumor progression differently depending on the type of malignancies. Several studies have explored the relationship between HCP5 and metastasis and prognosis in cancer ( 64 ). It was reported by Jiang et al that HCP5 was highly expressed in tumor tissues of LUAD patients and contributed to epithelial-mesenchymal transition (EMT) of LUAD cells, tumor growth, and metastasis, and was positively correlated with poor patient prognosis ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCP5 affects tumor progression differently depending on the type of malignancies. Several studies have explored the relationship between HCP5 and metastasis and prognosis in cancer ( 64 ). It was reported by Jiang et al that HCP5 was highly expressed in tumor tissues of LUAD patients and contributed to epithelial-mesenchymal transition (EMT) of LUAD cells, tumor growth, and metastasis, and was positively correlated with poor patient prognosis ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The field of lncRNAs had received a lot of press attention lately because of the accelerated advancement of high-throughput sequencing technologies ( Müller et al, 2015 ). Numerous studies have demonstrated that lncRNAs are implicated in tumorigenesis and development and are closely related to the prognosis of patients with tumors ( Ge et al, 2018 ; Hu et al, 2021 ). In previous meta-analyses, FOXP4-AS1 ( Zhang et al, 2022b ), SNHG15 ( Chen C. et al, 2020 ) and SNHG17 ( Zhang et al, 2022a ) were all linked to the clinicopathological characteristics and prognosis of various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that abnormal regulation of lncRNAs has been linked to the development and progression in a variety of human cancers [12,13]. Several lncRNAs, such as lncRNA HCP5, lncRNA TEX41, and lncRNA TTN-AS1, play important roles in the growth of malignant cells in SKCM [14][15][16]. In addition, there are a growing number of studies that point to the fact that abnormally expressed lncRNAs have been utilized as possible biomarkers for the diagnosis and prognosis of cancer [17,18].…”
Section: Introductionmentioning
confidence: 99%